Editors' Note. (28th February 2017) - Karam, Chafic; Griggs, Robert C.
Abstract : Editors' Note: In response to "Incident parkinsonism in older adults without Parkinson disease, " Mahlknecht et al. share their own experience of analyzing risk factors for parkinsonism in a separate population. They confirm and expand the study findings, providing additional single markers for prodromal Parkinson disease (PD).